Supercritical CO2 for the synthesis of nanometric ZIF-8 and loading with hyperbranched aminopolymers. Applications in CO2 capture. (March 2017) - López-Domínguez, Pedro; López-Periago, Ana M.; Fernández-Porras, Francisco J.; Fraile, Julio; Tobias, Gerard; Domingo, Concepción
Graphical abstract: A straight and high yield precipitation of empty-pore ZIF-8 nanopowder with tunable morphology is achieved via an environmentally friendly supercritical CO2 method. Highlights: ZIF-8 was precipitated using exclusively the green solvent CO2 in a one-pot synthesis. Particle size and morphology are controlled by varying ZIF-8 reagents ratio. Activated ZIF-8 with empty-pore is directly obtained, with surface area values close to the theoretical one. CO2 solvent can be also used to load the ZIF-8 micropores with hyperbranched aminopolymers. The amine loading increased the ZIF-8 CO2 adsorption in a 30 wt% by adding a chemisorption contribution. Abstract: ZIF-8 nanometric particles are prepared via an environmentally friendly supercritical method aimed to minimize the environmental impact of current developed technologies for the synthesis of metal organic frameworks. In this synthetic process, CO2 and ZIF-8 precursors are exclusively employed, avoiding the use of organic liquids, difficult to recover additives or large amounts of expensive ligand excess. The straight and high yield precipitation of empty-pore ZIF-8 nanopowder with tunable morphology was achieved. The powder was fully characerized in regard to the composition, structure, stability, morphology and textural properties. This work also focuses in the development of an eco-efficient method for the in situ polymerization of ethyleneimine inside the synthetized ZIF-8 pores, by using supercritical CO2 as a solvent, reaction medium and catalyst for the aziridine ring-opening. The use of the prepared materials in CO2 capture is assessed by analyzing CO2 adsorption isotherms.